2017
DOI: 10.1080/15384047.2017.1323581
|View full text |Cite
|
Sign up to set email alerts
|

miR-337 can be a key negative regulator in melanoma

Abstract: Incidence of melanoma is increasing annually worldwide. There remains a lack of suitable treatment methods which can significantly improve the 5-year survival rates of patients. It is established that micro RNAs (miRNAs) have important roles in the diagnosis and treatment of cancer. MiR-337 had been reported to regulate the development of variety of cancers, as a cancer suppressive factor. In our research we found that miR-337 had a lower expression in melanoma than adjacent tissues. The patients who had a low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…In this study, it was found that the expression of miR-337 was downregulated in pancreatic cancer tissues and pancreatic cancer cells, which was consistent with another research that miR-337 expression was suppressed in pancreatic cancer tissues [11]. MiR-337 has been reported to exert an inhibitory effect on some tumors such as melanoma and cervical cancer [15,20]. We further investigated the influence of miR-337 on pancreatic cancer cells.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, it was found that the expression of miR-337 was downregulated in pancreatic cancer tissues and pancreatic cancer cells, which was consistent with another research that miR-337 expression was suppressed in pancreatic cancer tissues [11]. MiR-337 has been reported to exert an inhibitory effect on some tumors such as melanoma and cervical cancer [15,20]. We further investigated the influence of miR-337 on pancreatic cancer cells.…”
Section: Discussionsupporting
confidence: 90%
“…MicroRNAs (miRNAs) are non‐coding short RNAs that regulate gene expression and negatively impact the stability and translation of mRNAs by binding to complementary sequences at 3′ untranslated region (3′UTR) 10 . It was reported that miR‐137 acted as a tumour repressor in malignant melanoma, 11 and miR‐337 was demonstrated to be a vital negative regulator in melanoma 12 . As one of the miRNAs, miR‐495‐3p was involved in the development of melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…STAT3 expression has been related to tumor metastasis and cellular apoptosis in various cancers mediated by miR-337 [7,9,12]. Therefore, we determined the effect of miR-337 expression on STAT3 in CTCL cells.…”
Section: Mir-337 Targeted the 3′-untranslated Region (Utr) Of Stat3mentioning
confidence: 99%
“…Studies have demonstrated the downregulation of miR-337 expression in many cancers [7][8][9][10][11][12]. Notably, miR-337 has been reported to mediate the expression of Janus kinase 2 (JAK2) and signal transducer and activator of transcription 3 (STAT3) in non-small cell lung cancer, melanoma, and hepatocellular carcinoma cells [7,9,12].…”
Section: Introductionmentioning
confidence: 99%